Understanding Multiplication: Should We Memorise It or Not? - Ernawati (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
Multiplication might be considered as one of the basic mathematical facts that should be mastered as its major role is to help children understanding more advanced concept of mathematics. For example, multiplication could be found in fractions, irrationals, polynomials, vectors, and matrices. Some might suggest memorising multiplication facts may help children to develop their automaticity in computation. However, some others said understanding multiplication should be prioritised over memorisation since it will make the children capable to apply it when they work with complex problems. For this reason, examining whether children should memorise multiplication or not might be useful to help the learning process. In this article, I synthesise two theories which seem contradictory. The first theory is from Gray and Tall (1991) about proceptual understanding in mathematics and the second theory is dynamic instruction view from Byrnes and Wasik (1991). I found that these two theories can be made to complement each other in learning multiplication.